Three brothers, headmen of the Chilkat, Alaska, 1907 - University of Washington Libraries
Three Chilkat leaders, identified as Ka-sh-ak, Skan-doo, and Ind-a-yanek (Swatka) pose together wearing their ceremonial clothing. Two of the brothers have elaborately-patterned Chilkat blankets, and the third wears a shirt decorated with deer hoofs. The man in the center also displays a carved wooden bird helmet with feathers attached. Each man holds a carved and painted bird-shaped rattle. The Chilkat are a coastal Tlingit people. Caption on image: "Three brothers, old head-men of the Kak-von-tons of the Chilkat Tribe. Ka-Sh-Ak, the Monkey-Man; Skan-Doo, notorious old medicene [sic] man; Ind-A-Yanek (Swatka) the famous Indian guide" "Copyright 1907 by Case & Draper." Photographers W.H. Case and Horace H. Draper began their partnership at Skagway, Alaska around 1898, during the Klondike gold rush. In 1901, the firm photographed the scenery along the White Pass & Yukon Route; in 1905 the studio opened a branch in Juneau. When the partnership dissolved in 1908, Case took charge of the Juneau studio. (University of Washington Special Collections from information supplied by the Alaska State Historical Library)